PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. SUKSES MANDIRI SENTOSA (SMS) SEMARANG - Agus Heriyanto, 09.05.51.0105 (Students Journal of Economic and Management, 2014)
The purpose of this study is to examine and analyze the effect of motivation, work environment and compensation on employee performance. The population in this study were employees of PT. Success Mandiri Sentosa (SMS), Jl. No. Sentono Raya 20 Banjardowo Genuk Semarang totaling 133 employees. The sample in this study was 57 employees. Engineering samples in this study were randomized. Primary data types and methods of data collection questionnaire. The analysis technique used is multiple regression. The results showed that: (1). Motivation significant effect on employee performance. (2). Work environment have a significant effect on employee performance. (3). Compensation significant effect on employee performance Keywords : Motivation, Work Environment, Compensation, Employee Performance